Glee the concert movie [videorecording (DVD)]. - Monteith, Cory, 1982-2013; Colfer, Chris, 1990-; Lynch, Jane, 1960- (20th Century Fox Home Entertainment, 2011)
Here's your front-row seat to a thrilling concert performed by the phenomenally talented cast of Glee. See your favorite stars from the hit TV show as they sing the songs you love and dance up a storm on stage. Get swept up in the energy of Glee Live, including performances not seen in theaters and exclusive interviews! Bonus features included.